2017
DOI: 10.1387/ijdb.170037af
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ALK1 family of type I BMP/ADMP receptors during gastrula stages in Xenopus embryos

Abstract: Multiple members of the transforming growth factor beta (TGFβ) family of secreted factors play central inductive and patterning roles during embryogenesis. During gastrulation in vertebrates, the bone morphogenetic protein (BMP) sub-family is linked to formation of the embryonic organizer, Spemann's organizer in Xenopus, and dorsal-ventral mesoderm patterning. Our knowledge regarding the BMP receptors mediating this signaling is still very incomplete. The BMPR1A (ALK3) and BMPR1B (ALK6) receptors are known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…ADMP has been shown to bind the type I receptor, ACVR1 (ALK2) [ 17 ], while the common BMP receptors, BMPR-Ia (ALK3) and BMPR-Ib (ALK6) and the type II receptor, BMPR-II, do not bind ADMP or inhibit its activity [ 17 , 21 ]. We have recently shown that Alk2 is expressed within the organizer and it is co-expressed with ADMP [ 19 ]. As the putative, dorsal ADMP receptor, ALK2 should be involved in the organizer-promoting function of ADMP (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…ADMP has been shown to bind the type I receptor, ACVR1 (ALK2) [ 17 ], while the common BMP receptors, BMPR-Ia (ALK3) and BMPR-Ib (ALK6) and the type II receptor, BMPR-II, do not bind ADMP or inhibit its activity [ 17 , 21 ]. We have recently shown that Alk2 is expressed within the organizer and it is co-expressed with ADMP [ 19 ]. As the putative, dorsal ADMP receptor, ALK2 should be involved in the organizer-promoting function of ADMP (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we focused on ALK1 (ACVRL1) as a putative second ADMP receptor. Recently we described the Alk1 expression pattern during early gastrula [ 19 ]. Alk1 is a weakly expressed gene during gastrula stages, and its transcripts are most abundant in the lateral marginal zone (LMZ), just flanking the organizer domain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations